Three-Dimensional Pore-Scale Simulation of Flow and Thermal Non-Equilibrium for Premixed Gas Combustion in a Random Packed Bed Burner - Jinsheng Lv; Junrui Shi; Mingming Mao; Fang He (Energies, 2021)
Pore-scale studies of premixed gas combustion in a packed bed is conducted to study the flow and thermal non-equilibrium phenomenon in packed bed. The 3D random packed bed is generated using the EDEM software and solid surface radiation is computed using Discrete Ordinates (DO) model. The simulations are carried out using a commercial software package based on the finite volume method. It is shown that the local variation of species mass fraction, reaction rate et al. in pores near the flame front is significant, the radiation heat flux is transferred layer-by-layer. Cold flow simulation without reaction reveals that flow non-equilibrium is one of the essential characteristics of packing bed and increase in flow velocity leads to intensify non-equilibrium phenomenon. The distributions for content of axial velocity and gas temperature are wave-like shape in the burner and vary with time.